Supraventricular and ventricular arrhythmias: interventional management. (October 2018) - Gopal, Razeen; Muggenthaler, Martina; Gall, Nicholas; Schilling, Richard
Abstract: Cardiac electrophysiology is the subspecialty of cardiology dealing with heart rhythm disorders, particularly the investigation and management of bradyarrhythmias and tachyarrhythmias, syncope and the prevention of sudden cardiac death. Recent technological developments include ever smaller and more complex implantable pacing devices, as well as the ability to map an arrhythmia circuit in three dimensions, potentially in one beat, and to safely destroy small areas of myocardium known to be critical to a particular arrhythmia. These have led to a dramatic expansion in ability to treat heart rhythm problems. This article focuses on some of the treatment strategies.